The Panca Pramana Learning Model for Scientific Literacy and Critical Reasoning in Fourth Grade Elementary School Students - Ni Made Alit Arisandi; I Gede Astawan; Ni Ketut Desia Tristiantari (Universitas Pendidikan Ganesha, 2025)
The low level of scientific literacy and critical reasoning among elementary school students indicates that learning practices have not yet optimally fostered active engagement and meaningful conceptual understanding. Instruction that is predominantly teacher-centered tends to limit students’ opportunities to observe, reason, and construct knowledge independently. This study aims to analyze and examine the effectiveness of the Panca Pramana learning model on students’ scientific literacy and critical reasoning skills at the elementary school level. This research employed a quasi-experimental approach using a nonequivalent pretest–posttest control group design. The research subjects consisted of 34 students divided into an experimental group and a control group selected through random sampling. Data were collected using multiple-choice and essay tests designed to measure scientific literacy and critical reasoning skills. Inferential statistical analysis was applied to determine differences in learning outcomes between the two groups. The findings indicate that the implementation of the Panca Pramana learning model has a significant positive effect on improving students’ scientific literacy and critical reasoning compared to conventional instruction. These results suggest that the Panca Pramana model can serve as an effective innovative learning alternative to support the development of 21st-century competencies in elementary education.